Field of graves [large type] - Ellison, J. T. (Ellison, J. T. Taylor Jackson novel., 2016)
A serial killer is targeting young Vanderbilt University coeds, one of whom is the daughter of a major university benefactor and Texas oilman. Lt. Taylor Jackson, Nashville cop, and Dr. Samantha Owens, medical examiner, face a huge public relations nightmare. Taylor, struggling with departmental strife, is asked to partner with troubled FBI profiler Dr. John Baldwin, who is back in Tennessee after a disastrous investigation accident. Together, they must work around the clock to find the killer before another girl dies.